A necessária reformulação da organização e do processo nos Tribunais de Contas para efetivo alcance dos princípios do devido processo legal, do contraditório e da ampla defesa - Salles, Alexandre Aroeira (2017)
The Brazilian Constitution of 1988 provided the Brazilian Courts of Accounts with important competencies for the external control of public expenditures, including the function of judging the accounts of those who use, collect, store, and administer public resources, and the power to impose sanctions and order the return of amounts spent improperly. At the same time, the 1988 Brazilian Constitution, through its Article 5, guarantees to all individuals that the State can only deprive them of their assets and rights if it faithfully follows certain specific principles (“normas-princípio”) of due legal process, adversarial system and full defense. Disrespecting directly such principles, the TCU Organic Law (Law 8.443/92) structured the Federal Court of Accounts in such a way as to give to thejudges (”Ministers”) of the Court the role of auditing, accusing, instituting, instructing, administering the evidence and deciding on its accusatory proceedings against individuals. Moreover, the Law established a process in which the parties cannot: produce their evidence; analyse the evidence presented by their accusers/judges; be heard; or even appeal to a forum that has not already reviewed and decided on their case. Therefore, it is necessary to change Law 8.443/92 to enable the creation of a structure and process in the Federal Court of Accounts that is fair (as well as the laws of all other state and municipal Courts of Accounts), including among the responsibilities of the members of the Public Prosecutor's Office of Accounts auditing, accusing, and guaranteeing that the parties produce fully their evidence and counter-evidence, freeing the Ministers to fulfill the exclusive function of judging impartially, based on the procedural dialectic